Temporal and spectral variation of aerosol optical depth (AOD) over Manila - Macalalad, Ernest P. (Animo Repository, 2022)
Aerosol optical depths for four wavelengths (368, 500, 675, 862 nm) were obtained using a commercial sunphotometer over Manila. A total of 33 values of mean AOD were calculated in the morning (11) and afternoon (22) sessions from 1 March to 2 April 2004 in DLSU-Manila. The more of the shorter wavelengths than the longer ones.